2016
DOI: 10.1007/s10545-016-9990-5
|View full text |Cite
|
Sign up to set email alerts
|

International clinical guideline for the management of classical galactosemia: diagnosis, treatment, and follow‐up

Abstract: Classical galactosemia (CG) is an inborn error of galactose metabolism. Evidence-based guidelines for the treatment and follow-up of CG are currently lacking, and treatment and follow-up have been demonstrated to vary worldwide. To provide patients around the world the same state-of-the-art in care, members of The Galactosemia Network (GalNet) developed an evidence-based and internationally applicable guideline for the diagnosis, treatment, and follow-up of CG. The guideline was developed using the Grading of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
1
23

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(208 citation statements)
references
References 1 publication
6
165
1
23
Order By: Relevance
“…Berry, 2014; Welling et al, 2017). Once solid foods are introduced, however, some children continue on a diet that rigorously excludes not only milk and all high galactose dairy products but also legumes, many fruits and vegetables, and other foods believed to contain concerning amounts of galactose.…”
Section: Introductionmentioning
confidence: 99%
“…Berry, 2014; Welling et al, 2017). Once solid foods are introduced, however, some children continue on a diet that rigorously excludes not only milk and all high galactose dairy products but also legumes, many fruits and vegetables, and other foods believed to contain concerning amounts of galactose.…”
Section: Introductionmentioning
confidence: 99%
“…Вроджена недо-статність одного з трьох ферментів [1]: галактозо-1-фосфатуридинтрансферази (ГАЛТ; GALT), галактокінази (ГАЛК; GALK) і уридиндифосфат-галактозо-4-епімерази (ГАЛЕ; GALE) призводить до накопичення галактозо-1-фосфату, галактози і галактитолу в еритроцитах, клітинах печінки та ін-ших тканинах, що впливає на осмотичні процеси, спричиняє виникнення набряків, тяжкого уражен-ня печінки, нервової системи, катаракти, сепсису [3]. Сучасна класифікація галактоземій побудована за етіологічним принципом [4] (табл.…”
Section: вступunclassified
“…Детекція мажорних мутацій Q188R і K285N [20] в гені GALT здійснена за допомогою алельспеци-фічної полімеразної ланцюгової реакції на термо-циклері SimpliAmp (AB, США) з використанням праймерів [3] та комерційних наборів GenPak PCR Core (Neogen, Україна). Візуалізацію та реєстра-цію результатів здійснено за допомогою капіляр-ного електрофорезу MultiNA (Shimadzu Biotech, Японія).…”
Section: матеріали та методиunclassified
“…1,21,22 It is unclear whether this condition is clinically benign or may require lactose restriction, 1,21,22 however, the latest clinical guidelines for the management of patients with galactosemia do not recommend treatment for patients with DG variant galactosemia. 23 …”
Section: Clinical Description Of Disease Galt Deficiency (Classic Galmentioning
confidence: 99%
“…Early studies demonstrated that, although both urinary galactitol and Gal-1-P are greatly increased in patients with classic galactosemia, urinary galactitol may be a better marker of dietary compliance; 20,48,49,52 however, the clinical utility of galactitol for managing patients with classic galactosemia is still considered limited. 23 …”
Section: Metabolitesmentioning
confidence: 99%